Investigating the Metacognitive Strategies During Post-Editing Translation Process: An Application of Think-Aloud Protocols (TAP) - Indarti, Dwi (JOLLT Journal of Languages and Language Teaching, 2024)
Metacognition, the reflection on thinking processes, plays a crucial role in cognitive activities. This study delves into metacognitive strategies employed during post-editing in the translation process, particularly focusing on English-Indonesian translation through the application of think-aloud protocols (TAP). The investigation encompasses planning, monitoring, and evaluation as interconnected phases of metacognitive strategies. A qualitative case study method is employed, with a university student as the participant. Data analysis involves coding and categorizing using a thematic analysis approach, based on the metacognitive strategies framework. The findings show that the participant employes the components of planning such as evaluate the necessity of post-editing, applied knowledge on the specific post-editing cases, and identified the goal and the necessity for having specific post-editing, the components of monitoring such as using facts and instruction learned previously, making changes for a better translation product, and self-monitoring of progress, and elements of evaluating, such as deep level revising to produce better post-editing, and taking action to collect extra information. Pedagogical implications highlight the potential for enhancing learning experiences and improving translation skills through explicit instruction, modeling and systemic strategy training. The study concludes by emphasizing the importance of metacognitive flexibility, cultural influences, and adaptive strategic behavior in post-editing, shaping a roadmap for learners to navigate challenges and continually refine their approach.